A successful cesarean section followed with endovascular stent-graft implantation for a 36-week twin pregnancy with acute aortic dissection: a case report. (August 2016) - Hao, Qun; Wang, Hao; Zhang, Cheng; Ma, Ai-qing; Wu, Yuan-zhe
Abstract Introduction It is a first case report for a woman pregnant with twins who suddenly ruptured with a Stanford type B aortic dissection. Materials and methods A 24-year-old pregnant patient gravida 1 and para 0 at the 36th gestation week was sent to our Emergency Department under the medical monitoring by the local gynecologist. Her primary complaints were that she suddenly felt "severe tearing chest pain". Ultrasound image illustrated fetal twins at cephalic positions about 36th gestation week. An emergent magnetic resonance angiography (MRA) of aorta is given below: dissection of the descending aorta arisen from the descending aorta to the bifurcation of abdominal aorta suggestive of Stanford type B aortic dissection. Results The two babies were delivered by an emergent cesarean section and stent-graft placement of the descending thoracic aorta was performed on the mother thereafter. Conclusion This case report illustrates the value of comprehensive multidisciplinary discussion and collaboration among different departments to make quick decisions. Endovascular stent-graft repair may be the best option for the treatment of Stanford type B aortic dissection in late pregnancy.